Peran Jaksa Selaku Penyidik Dan Penuntut Umum Dalam Mempercepat Penyelesaian Perkara Tindak Pidana Korupsi (Studi Pada Kejaksaan Negeri Medan) - Erman Syafrudianto; Madiasa Ablizar; Edi Yunara; mahmud mulyadi (Iuris Studia: Jurnal Kajian Hukum, 2021)
Amid the government efforts to eradicate corruption each year that was formulated in the acceleration corruption eradication program, government and law enforcement agencies were defiant. On one side, the people still believe and wish for the better effort and work hard in progressing the criminal corruption act, bring the cases to the court, and prosecute the perpetrator such crimes based on the Laws so the perpetrator could generate a deterring effect. On the other side, there are a lot of people who assume the law enforcement agencies performance in eradicating corruption are slow and not appropriate within public expectations. Even a little of accusation and mocking deliver to law enforcement agencies that have been working as maximum as possible in revealing to corruption act with several kinds of problems which affect the law process obstacles.The Attorney, one of the law enforcement agencies based on chapter 2 article 1 Law Number 16 of 2004 on Attorney of The Republic of Indonesia that mentioned “The Attorney of The Republic of Indonesia which next in Laws called Attorney is the government agency that performs state powers in enforcing and other authorities based on the Laws,” have legitimation in attempt to accelerating corruption eradication.The formulation of problems in the research was referred to the Article 25 Law Number 31 of 1999 concerning Eradication of Criminal Act of Corruption that was mentioned: “The indictment, prosecution, and interrogation within a court session of a corrupt act shall be conducted on the basis of the existing criminal law procedures unless otherwise stipulated.” The regulation was clearly to prioritize attempting corruption act had to finish immediately in acceleration and punctuality. Looking at the fact, they are not as easy as to imagine many scholars. The settlement of corruption cases act is challenging with several factors, juridical and non-juridical, thus the need for effective ways to combating problems that referred to existing the Laws.